Detection of Mouse Mammary Tumor Virus-Like Sequence (MMTVLike Sequence) in the Breast Cancer of Iraqi Women Samples by Nested PCR. - Asaad Al-janabi; Ahmed Mohammed Ali Nazar; Hashim Raheem Tarish (Kufa Journal for Nursing Sciences)
Background: Since the discovery of MMTV in the high cancer strains of mice capable of initiating mammary tumors, and its subsequent identification as a B-type RNA virus, several evidence has been accumulated supporting the attractive hypothesis that a similar agent is associated with human breast cancer. The current study conducted to detection the MMTV-LIKE SEQUENCE (MMTV-like virus) by nested PCR.